Ancient plant remains with special reference to buckthorn, Frangula alnus Mill., pyrenes from Dascyleum, Balikesir, NW Turkey - (:unkn) unknown (POLSKIE TOWARZYSTWO BOTANICZNE, 2017)
Carbonized plant remains recovered from the ancient city Dascyleum (Daskyleion) in the province of Balikesir in northwestern Turkey provide an outline of several phases of plant use in archaic, Hellenistic, and medieval times. At the study site, various crop plant remains of Near Eastern agriculture, including cereals (barley, Hordeum vulgare L. and bread/durum/rivet wheat, Triticum aestivum L. / T. durum Desf. / T. turgidum L.) and pulses [bitter vetch, Vicia ervilia (L.) Willd.; grass pea, Lathyrus sativus L. / L. cicera L.; fava bean, V. faba L.; and chickpea, Cicer arietinum L.] were found. Drupaceous fruits and pyrenes of buckthorn (Frangula alnus Mill.) were also found, probably representing dyes and/or medicines used by the inhabitants of the mound. Archaeometrical analyses of the ancient buckthorn pyrenes by high performance liquid chromatography with photodiode array detector (HPLC-PDA) provide chemical evidence for traces of ancient mordants remaining until the present day. Some of the pulse seed remains retrieved from the medieval layers at the study site were found to have been infested by bruchid beetles (Bruchidae).
Keywords: archaeobotany; archaeometry; ancient buckthorn; Daskyleion; Turkey; NATIONAL-PARK; LAKE MANYAS; MARMARA SEA; ALPINE ZONE; ANATOLIA